Program Peningkatan Keamanan Di Bandara Kualanamu Medan Apabila Beroperasi - Ismail Nadjamuddin (Research and Development Agency of The Ministry of Transportation, 2012)
Kualanamu Medan Airport Construction is an alternative to overcome the operational limitations and the land that was experienced Polonia Airport. Airport security enhancement program Kualanamu Medan when operating include airport security aspects of the provision of facilities consisting of: X-Ray facility 12 units, Walk Throught Metal Detector (WTMD) 14 units, Hand Held Metal Detector (HHMD) 24 units, Closed Circuit Television (CCTV , Explosive Detection System 2 units, 2 units Liquit Scan Detecto,, Detector Nubikara 2 units (Nuclear, Biological, Chemical, Radio Active), Body Scane 1 unit, Body Inspector, Airport For Perimeter Surveillance, Security Inspection Car and Motorcycle 4. The security officer in Medan Airport Kualanamu totaling 204 personnel consisting of 124 personnel from the PT. Angkasa PuraII, 40 BKO-military personnel who assisted and 40 staff personnel outsoursing. The system and airport security procedures will refer to the Regulation of the Minister of Transportation No. 9 of 2010 about the National Aviation Security Programme and ICAO in Annex17 on Security and Document-8973 on the Security Manual for Safeguarding Civil Aviation Against Acts of Unlawful Interference, that the safety and security systems at airports should be the maximum, using equipment and adequate procedures that ensure safety and smooth flight. Pembangunan Bandara Kualanamu Medan merupakan alternatif untuk mengatasi keterbatasan operasional dan tanah yang dialami Bandara Polonia. Program peningkatan keamanan bandara Kualanamu Medan saat dioperasikan meliputi aspek keamanan bandara, penyediaan fasilitas yang terdiri dari: 12unit fasilitas X-Ray, 14 unit Walking Through Mental Detector (WTMD), 24 unit Hand Held Metal Detector (HHMD), 2 unit Closed Circuit Television (CCTV)dan sistem Deteksi peledak, 2 unit Liquit Pindai Detecto, 2 unit Detector Nubikara (Nuklir, Biologi, Kimia, Radio Aktif), Badan Scane 1 unit, Bandara Untuk Surveillance Perimeter, 4 Mobil Keamanan Inspeksi dan Sepeda Motor petugas keamanan di Medan Bandara Kualanamu sebesar 204 personel yang terdiri dari 124 personil dari PT Angkasa Pura II, 40 BKO-personil militer yang dibantu dan 40 personil staf outsoursing. Sistem dan prosedur keamanan bandara akan mengacu pada Peraturan Menteri Perhubungan Nomor 9 tahun 2010 tentang National Aviation Security Program dan ICAO dalam Annex-17 tentang Keamanan dan manual dokumen-8973 tentang Keamanan Penerbangan Sipil upaya pelanggaran hukum, bahwa keamanan dan sistem keamanan di bandara harus maksimal , menggunakan peralatan dan prosedur yang memadai yang menjamin keamanan dan kelancaran penerbangan.